Toxicity effects of magnesium oxide nanoparticles: a brief report - Rempel,Suzana (2020)
ABSTRACT In this work, magnesium oxide nanoparticles were synthesized by the sol-gel route and their ecotoxicity was tested in worms of the Eisenia andrei species. Magnesium oxide nanoparticles were characterized by XRD, surface area via BET, TEM and SEM-FEG/EDS. The lethality test with Eisenia andrei earthworm species followed the recommendations of ISO 11268-1 (ISO, 2012) in a completely randomized design with six replicates for each concentration tested (1.06, 2.12, 4.24, 8.48 and 16.96 μg of NPs-MgO/kg of soil), plus the control. The concentrations were mixed to the tropical natural soils, Entisol Typic Quartzipsamments and Oxisol, with no agricultural use history. The morphological and structural analyses of the nanoparticles indicated the formation of magnesium oxide with cubic structure, constituting agglomerates of nanostructures of the order of 20 to 50 nm. The results of toxicity were submitted to analysis of variance (ANOVA One-way), followed by the Dunnett test (p <0.05). Based on standardized toxicological tests it was found that NPs-MgO, at the concentrations tested, did not affect the survival of Eisenia andrei species in the natural soils studied.